Effect of Dietary Ascorbic Acid on Performance of Broiler Chickens Exposed to Different Lighting Regime - Tuleun, C.D.; Njoku, P.C.; Okwori, A.I. (International Journal of Poultry Science, 2010)
A 2 x 2 factorial experiment was conducted to determine the performance of 400 Anak broiler chicks exposed to two lighting regimes viz. 12 h light:12 h darkness and 24 h light:0 h darkness and fed diets containing two levels of ascorbic acid (0 and 250 mg AA/kg of feed). Each treatment was replicated four times with 25 birds per replicate. Results showed that at the starter phase of growth, chicks on continuous lighting regime recorded significantly (p